A water-filled garment to protect astronauts during interplanetary missions tested on board the ISS. (August 2018) - Baiocco, G.; Giraudo, M.; Bocchini, L.; Barbieri, S.; Locantore, I.; Brussolo, E.; Giacosa, D.; Meucci, L.; Steffenino, S.; Ballario, A.; Barresi, B.; Barresi, R.; et al.
Abstract: As manned spaceflights beyond low Earth orbit are in the agenda of Space Agencies, the concerns related to space radiation exposure of the crew are still without conclusive solutions. The risk of long-term detrimental health effects needs to be kept below acceptable limits, and emergency countermeasures must be planned to avoid the short-term consequences of exposure to high particle fluxes during hardly predictable solar events. Space habitat shielding cannot be the ultimate solution: the increasing complexity of future missions will require astronauts to protect themselves in low-shielded areas, e.g. during emergency operations. Personal radiation shielding is promising, particularly if using available resources for multi-functional shielding devices. In this work we report on all steps from the conception, design, manufacturing, to the final test on board the International Space Station (ISS) of the first prototype of a water-filled garment for emergency radiation shielding against solar particle events. The garment has a good shielding potential and comfort level. On-board water is used for filling and then recycled without waste. The successful outcome of this experiment represents an important breakthrough in space radiation shielding, opening to the development of similarly conceived devices and their use in interplanetary missions as the one to Mars.